The impact of truss structure on stiffness by finite element method - Ehsan Ketabi (Regional Information Center for Science and Technology (RICeST), 2017)
In this study was to evaluate the impact of the truss structure on stiffness and stress distribution in the truss structural members. Made and synchronizes this structures with any Populus_ Nigra lumbers, in finally made 44 truss structure with 11 varying samples and 4 replicates. were used by two joint like friction joints was created with Glue stick and dual joint was created with nails to the 4.5 cm and calculate the resistance trusses structures by mechanical testing machine with 12.5 mm/min loading speed and 3.5 KN than mechanical test results showed, Hip Girder truss most resistance stress distribution and were the least impact on the strength and distribution of tension truss structure is significant in 95%. To show the stress distribution on the members, modeling software was AutoCAD, Catia and finite element analysis software was ANSYS. In finally the results show that maximum stress concentration, failure to engage in experimental mode.